Epithelial Cell Inflammasomes in Intestinal Immunity and Inflammation - Lei-Leston, Andrea C.; Murphy, Alison G.; Maloy, Kevin J. (Frontiers in Immunology, 2017)
Pattern Recognition Receptors (PRR), such as NOD-like receptors (NLR), sense conserved microbial signatures and host danger signals leading to the coordination of appropriate immune responses. Upon activation, a subset of NLR initiate the assembly of a multimeric protein complex known as the inflammasome, which processes pro-inflammatory cytokines and mediates a specialised form of cell death known as pyroptosis. The identification of inflammasome-associated genes as inflammatory bowel disease (IBD) susceptibility genes, implicates a role for the inflammasome in intestinal inflammation. Despite the fact that the functional importance of inflammasomes within immune cells has been well established, the contribution of inflammasome expression in non-hematopoietic cells remains comparatively understudied. Given that intestinal epithelial cells (IEC) act as a barrier between the host and the intestinal microbiota, inflammasome expression by these cells is likely important for intestinal immune homeostasis. Accumulating evidence suggests that the inflammasome plays a key role in shaping epithelial responses at the host-lumen interface with many inflammasome components highly expressed by IEC. Recent studies have exposed functional roles of IEC inflammasomes in mucosal immune defence, inflammation and tumorigenesis. In this review, we present the main features of the predominant inflammasomes and their effector mechanisms contributing to intestinal homeostasis and inflammation. We also discuss existing controversies in the field and open questions related to their implications in disease. A comprehensive understanding of the molecular basis of intestinal inflammasome signalling could hold therapeutic potential for clinical translation.